Implikasi Terapi Cairan dalam Transplantasi Ginjal pada Pasien dengan Penyakit Ginjal Kronis : Narative Review - Suandika, Made; Inaya, Filia Nadira; Ramadhan, Sidqi Rassis (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Kidney transplantation is the treatment of choice for patients with end-stage chronic kidney disease. The success of this procedure is highly influenced by appropriate perioperative fluid management. Fluid imbalance can lead to serious complications, including delayed graft function, impaired renal perfusion, and increased postoperative morbidity and mortality. This review aims to evaluate the current evidence on perioperative fluid therapy strategies in kidney transplantation, focusing on fluid type selection, monitoring methods, and clinical implications. A narrative review was conducted by synthesizing recent studies on fluid management in patients with chronic kidney disease undergoing kidney transplantation. The findings show that balanced crystalloids are preferred over 0.9% sodium chloride because they improve acid–base balance and renal perfusion. In addition, goal-directed fluid therapy guided by dynamic hemodynamic parameters helps maintain intraoperative hemodynamic stability. The combination of these approaches is associated with reduced postoperative complications and improved graft function. In conclusion, optimal perioperative fluid management plays a crucial role in improving kidney transplant outcomes. An individualized approach based on patient hemodynamic status, surgical phase, and graft characteristics should be applied to achieve better, safer clinical outcomes consistent with current evidence-based practice. The clinical implications highlight the need for standardized perioperative fluid management protocols across transplant centers to improve patient safety, reduce clinical practice variability, and support the consistent implementation of evidence-based guidelines in modern healthcare. This approach is also expected to enhance long-term patient outcomes and healthcare efficiency in referral hospitals through improved coordination of an integrated multidisciplinary clinical team.